Managing regime complexity: Introducing the interface conflicts 1.0 dataset - Julia Fuß; Christian Kreuder-Sonnen; Andrés Saravia; Michael Zürn (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2021)
The increasing density and entanglement of international law and institutions leads to a growing potential for collisions between norms and rules emanating from different international institutions. It is an open question, however, when actors actually create manifest conflicts about overlapping norms and rules and how - and with what consequences - such conflicts are handled. We therefore utilize the concept of "interface conflicts" in which two or more actors express positional differences over the scope or prevalence of different international norms. Building on the findings of the DFG research group OSAIC (Overlapping Spheres of Authority and Interface Conflicts), we introduce the Interface Conflicts 1.0 dataset, which assembles information on 78 interface conflicts. The dataset provides information on the actors and norms at stake in interface conflicts and focuses specifically on their subsequent handling. It distinguishes co-operative from non-cooperative conflict management, and codes the institutional as well as distributional outcomes of all management efforts. Drawing on the Interface Conflicts 1.0 dataset, the paper discusses first descriptive statistics regarding the bones of contention in interface conflicts, distributions across types of conflict management, and conflict management effects on the legal and institutional arrangements in the areas at stake. We thus contribute empirical building blocks to debates about global (dis)order and open new avenues for future research.
https://doi.org/10.7802/2241
Keywords: 320; Interface Conflicts; Conflict Management; Authority; Liberal International Order; Database; Institutional Overlap